2019
DOI: 10.3390/antiox8110537
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Dietary Polyphenols and Type 2 Diabetes in a Cross-Sectional Analysis of the PREDIMED-Plus Trial: Role of Body Mass Index and Sex

Abstract: Overweight and obesity are important risk factors for type 2 diabetes (T2D). Moving towards healthier diets, namely, diets rich in bioactive compounds, could decrease the odds of suffering T2D. However, those individuals with high body mass index (BMI) may have altered absorption or metabolism of some nutrients and dietary components, including polyphenols. Therefore, we aimed to assess whether high intakes of some classes of polyphenols are associated with T2D in a population with metabolic syndrome and how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 34 publications
(43 reference statements)
3
23
1
2
Order By: Relevance
“…In a previous clinical trial, a high intake of polyphenol-rich foods for 8 weeks reduced glucose concentrations in plasma and increased insulin secretion in adults at high cardiovascular risk [ 39 ]. Moreover, in the PREDIMED trial, a higher intake of total polyphenols, total flavonoids, stilbenes, and some flavonoid subclasses was inversely and linearly associated with the incidence of type 2 diabetes [ 40 ], and in the PREDIMED-Plus trial, high intakes of some polyphenols were inversely associated with the prevalence of type 2 diabetes in adults with metabolic syndrome, particularly in overweight subjects [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous clinical trial, a high intake of polyphenol-rich foods for 8 weeks reduced glucose concentrations in plasma and increased insulin secretion in adults at high cardiovascular risk [ 39 ]. Moreover, in the PREDIMED trial, a higher intake of total polyphenols, total flavonoids, stilbenes, and some flavonoid subclasses was inversely and linearly associated with the incidence of type 2 diabetes [ 40 ], and in the PREDIMED-Plus trial, high intakes of some polyphenols were inversely associated with the prevalence of type 2 diabetes in adults with metabolic syndrome, particularly in overweight subjects [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…MetS is associated with a pro-inflammatory state, and it has been proposed that a low-fat dietary intervention inducing weight loss slightly reduces inflammatory biomarkers such as high-sensitive c-reactive protein (CRP), interleukin−6 (IL) and tumor necrosis factor alpha (TNF-α) levels [ 16 , 127 , 128 , 129 ]. These results are inconclusive, and the effects observed depend on weight loss and diet composition, particularly dietary fiber, fruits and vegetables [ 16 , 128 ]. Additionally, some studies observed that low-fat dietary interventions could improve the microbiome dysbiosis linked to MetS by increasing α-diversity [ 130 , 131 ].…”
Section: Low-fat Dietmentioning
confidence: 99%
“…Regarding the prevention of MetS, Godos et al also conducted a meta-analysis to demonstrate the preventive role of the promotion of healthy dietary patterns to reduce the prevalence of MetS [ 15 ]. Furthermore, some sub-studies from the PREDIMED-Plus cohort showed associations between some dietary components of the traditional Mediterranean Diet (MedDiet) and improvement in MetS components [ 16 , 17 , 18 , 19 , 20 ]. The aim of the present review was to analyze the potential benefits of different dietary approaches on MetS status and their use as efficient strategies to prevent and treat MetS and its comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…This baseline cross-sectional analysis included 6633 participants from the PREDIMED-Plus trial. They found in a case of proanthocyanidins for elderly Spanish women that there were significant and linear inverse associations in comparing extreme quartiles for overweight and obesity, recognized as important risk factors for T2D [ 30 ]. In another cohort study in Korea, Kim et al investigated the association between dietary flavonoid intake and the prevalence of obesity using body mass index (BMI), waist circumference, and percent body fat (%BF) among elderly Korean females.…”
Section: Resultsmentioning
confidence: 99%